Mast Cell Repopulating Ability Is Lost During the Transition From Pre-HSC to FL HSC - Yoshimoto, Momoko; Kosters, Astrid; Cornelius, Samuel; Valiente, Noemi; Cheng, Haizi; Latorre, Augusto; Nishida, Chika; Ghosn, Eliver E. B.; Kobayashi, Michihiro (Frontiers in Immunology, 2022)
Recent advances in developmental immunology have revealed a hematopoietic stem cell (HSC)-independent origin for various innate immune lineages, including mast cells (MCs). It is now established that adult bone marrow (BM) long-term HSCs do not regenerate MCs but, instead, the physiological production of MCs starts before the emergence of HSCs in the aorta-gonad-mesonephros (AGM) region and is mostly completed before birth. However, while the AGM region represents a major site of MC generation during ontogeny, whether the first emerging HSCs in the AGM or fetal liver (FL) possess the potential to regenerate MCs is unknown. Here, we combined three fate-mapping mouse models with detailed HSC transplantation assays to determine the potential of AGM and FL HSCs to produce MCs. We show that HSCs from E11.5 AGM and E12.5 FL efficiently repopulated MCs in recipients. In stark contrast, HSCs from ≥E14.5 FL failed to reconstitute MCs. An Endothelial (EC) fate-mapping study confirmed the EC origin of the majority of MCs. Additionally, our HSC-labeling showed that HSCs do not produce MCs in a physiological setting. Hence, although most MCs are generated and maintained via an HSC-independent pathway, the earliest HSCs to emerge in the AGM and seed the early FL can produce MCs, but only during a minimal time window. Our results challenge the stem cell theory in hematology and EC-derived mast cells may contribute to the pathogenesis of postnatal mast cell disorders.